The foundations of worldwide economic integration power, institutions, and global markets, 1850-1930 - Dejung, Christof.; Petersson, Niels P. (Cambridge studies in the emergence of global enterprise, 2013)
"Power, Institutions, and Global Markets -- Actors, Mechanisms and Foundations of World-Wide Economic Integration, 1850--1930 Christof Dejung and Niels P. Petersson The rapid expansion of world trade between 1850 and 1914, its difficult reconstruction during the 1920s, and its subsequent decline during the Great Depression are key themes in the current historiography of economic globalisation. But such scholarship has broadly focused on the changing volume of foreign trade between nation states, on macro-economic problems such as national tariff policies, and on the history of the advancement of transport and communication technologies. There have been very few discussion of global trade development between the 1850s and the 1930s from the perspective of economic actors below the nation-state level, which is to say actors conducting trading operations in everyday business life. Likewise, economic and business historians have broadly neglected the institutional framework both shaping and shaped by the enterprises involved in such everyday trade. Through such a shift of focus, the contributions in the present volume strongly suggest that in the late nineteenth and early twentieth centuries, global economic integration was far more than the result of supply and demand and ever more efficient means of transport and communications"--